The incorporation of youth to the physical-recreational activities in the community - Mariza Frómeta-Romero (Universidad de Guantánamo, 2016)
The paper addresses a controversial issue about how to enhance the integration of young people to the community "Ojo de Agua" in Baracoa municipality in the recreational physical activities as a way of contributing to their leisure time and improving their health, besides, with the organization and planning of different activities the programs, the variety of recreational sports, sport clubs and federations are increased. The system of educational activities developed, may enhance youth incorporation to physical and recreational activities as well as making more rational use of their leisure time and their physical well-being.